"A Refugee Pastor in a Refugee Church": Refugee-Refugee Hosting in a Faith-Based Context. Issue 1 (1st June 2021) - Lauterbach, Karen
Abstract: This article discusses "refugee-refugee hosting" in a faith-based context. It looks particularly at Congolese churches in Kampala, Uganda, that play a crucial role for Congolese refugees seeking refuge and protection. The article analyzes hybrid forms of hosting in a faith-based context and discusses the implications of this for how guest and host categories are perceived. Four different patterns of refugee-refugee hosting are explored in which the relationship between host and guest as well as pastor and church member differ. The article argues that social status and hierarchies are important for how hosting is practiced. Moreover, religious ideas of gift giving, sacrifice, and reciprocity also influence hosting in this context.